Stroke warning signs perception, self-care behaviors and family support between controlled and uncontrolled hypertensions in the responsible area of Bang Krai Nai Sub-District Health Promoting Hospital, Nonthaburi Province - ขำเขียว รัฐกานต์; มัททวางกูร ชนิดา (Disease Control Journal, 2018)
The present study was aimed to compare the perception of stroke warning signs, blood pressure behavior and family support among controlled and uncontrolled hypertensive patients in the responsible area of Bang Krai Nai Sub-District Health Promoting Hospital, Nonthaburi Province. 230 simples who were diagnosed hypertension at least one year were collected from June 2016 to May 2017. Only 210 questionnaires were collected. The instruments used in data collection included demographic data form, perception of stroke warning signs, blood pressure controlled behavior and family support. Cronbach’s alpha correlation coefficient analyses revealed that the reliability of the instrument was 0.89. Data were analyzed using descriptive statistics and t-test. The study findings showed that the controlled and uncontrolled hypertensive groups had high and moderate level of perception of stroke warning signs ( = 3.50, SD = 1.28; = 3.26, SD = 1.13), respectively, both of them had lowest level of diet-risk behavior ( = 1.22, SD = 0.28; = 1.37, SD = 0.33, respectively), had moderate and low level of exercise behavior ( = 2.79, SD = 1.22; = 2.28, SD = 0.97), respectively, had high and moderate level in stress management behavior ( = 3.75, SD = 0.72; = 3.49, SD = 0.70), respectively, both of them had high level of drug-intake behavior and medical follow-up ( = 4.11, SD = 0.58; = 3.96, SD = 0.58, respectively) and had high and moderate level in family support ( = 3.63, SD = 1.61; = 3.32, SD = 1.24), respectively. Furthermore, the findings revealed that the perception of stroke warning signs, drug-intake behavior and medical follow-up and family support were not significantly different from the uncontrolled group at 0.05 (p = 0.158, 0.066 and 0.060, respectively). While the diet-risk behavior, exercised behavior and stress management behavior in controlled group were significantly different from the uncontrolled group at 0.05 (p = 0.000, 0.014 and 0.007, respectively). Thus, health personnel should continuously motivate the hypertensive patients to have proper diet-behavior, exercise behavior and stress management, especially in uncontrolled hypertensive patients.